THE MYTHOLOGIES OF THE HISTORICAL NOVEL (BASED ON EXAMPLES FROM POLISH LITERATURE AFTER 1945) - Tomczok, Paweł (Porównania, 2019)
The article attempts to research the images of historical novelists in the post-war period of Polish literature. The basis of the research is a collection of interviews, prefaces, afterwords and criticisms by such authors as Teodor Parnicki, Hanna Malewska, Antoni Gołubiew, Elżbieta Cherezińska and Marcin Wolski. Their opinions are selected in four domains that defined the possible positions that could be taken by the historical novelists when they talked about their work. These four domains define the mythology of the historical novel as well as the possibilities of building a specific anti-myth based on the negation of the basic determinants of the way literature speaks about the past.